Reduced body weight of Pacific saury (Cololabis saira) causes delayed initiation of spawning migration. (8th March 2022) - Kakehi, Shigeho; Hashimoto, Midori; Naya, Miyako; Ito, Shin‐ichi; Miyamoto, Hiroomi; Suyama, Satoshi
Abstract: The fishing grounds of the Pacific saury began shifting eastward after 2013 and deviated further east in 2019 and 2020. Consequently, the migration pattern from the pre‐fishing distribution to fishing grounds may be changing. This study investigated inter‐annual variations in westward spawning migration parameters using a migration model. Case studies were conducted to estimate optimal values for the initiation date of spawning migration and migration speed during spawning migration. The estimated optimal initiation date of spawning migration from 2003 to 2018 was July 13 to August 8, with an average of July 31. However, in 2019 and 2020, the initiation date of spawning migration was August 22 and September 5, respectively, significantly later than that in 2003–2018 ( p < .01). The estimated optimal swimming speed during spawning migration in 2019 and 2020 was not significantly different from that in 2003–2018 ( p > .7). These results indicate that delays in the initiation of spawning migration occurred in 2019 and 2020, leading to an eastward shift of fishing grounds. The mean body weight of the age‐1 Pacific saury in the pre‐fishing season had a significant negative correlation ( p < .01) with the initiation date of spawning migration. This result suggests that Pacific saury with low body weight continues to feed for growth instead of initiating spawning migration. However, body weight at initiation of spawning migration had a significant decreasing trend ( p < .01), indicating that the Pacific saury had to start spawning migration despite low body weight in recent years.